Respuesta :
Answer:
Part a)
Velocity of sled
[tex]v = \frac{m_1 s}{m_1 + m_2 + M}[/tex]
velocity of first man who jump off
[tex]v_1 = -\frac{(m_2 + M) s}{m_1 + m_2 + M}[/tex]
Part b)
Velocity of sled
[tex]v_f = (\frac{m_1 s}{m_1 + m_2 + M}) + (\frac{m_2}{m_2 + M})s[/tex]
Also the speed of second person is given as
[tex]v_2 = (\frac{m_1 s}{m_1 + m_2 + M}) - \frac{Ms}{m_2 + M}[/tex]
Part c)
change in kinetic energy of sled + two people is given as
[tex]KE = \frac{1}{2}Mv_f^2 + \frac{1}{2}m_1v_1^2 + \frac{1}{2}m_2v_2^2[/tex]
Explanation:
As we know that here we we consider both people + sled as a system then there is no external force on it
So here we can use momentum conservation
since both people + sled is at rest initially so initial total momentum is zero
now when first people will jump with relative velocity "s" then let say the sled + other people will move off with speed v
so by momentum conservation we have
[tex]0 = m_1(v - s) + (m_2 + M)v[/tex]
[tex]v = \frac{m_1 s}{m_1 + m_2 + M}[/tex]
so velocity of the sled + other person is
[tex]v = \frac{m_1 s}{m_1 + m_2 + M}[/tex]
velocity of first man who jump off
[tex]v_1 = \frac{m_1 s}{m_1 + m_2 + M} - s[/tex]
[tex]v_1 = -\frac{(m_2 + M) s}{m_1 + m_2 + M}[/tex]
Part b)
now when other man also jump off with same relative velocity
so let say the sled is now moving with speed vf
so by momentum conservation we have
[tex](m_2 + M)(\frac{m_1 s}{m_1 + m_2 + M}) = m_2(v_f - s) + Mv_f[/tex]
[tex](m_2 + M)(\frac{m_1 s}{m_1 + m_2 + M}) + m_2s = (m_2 + M)v_f[/tex]
Now we have
[tex]v_f = (\frac{m_1 s}{m_1 + m_2 + M}) + (\frac{m_2}{m_2 + M})s[/tex]
Also the speed of second person is given as
[tex]v_2 = (\frac{m_1 s}{m_1 + m_2 + M}) + (\frac{m_2}{m_2 + M})s - s[/tex]
[tex]v_2 = (\frac{m_1 s}{m_1 + m_2 + M}) - \frac{Ms}{m_2 + M}[/tex]
Part c)
change in kinetic energy of sled + two people is given as
[tex]KE = \frac{1}{2}Mv_f^2 + \frac{1}{2}m_1v_1^2 + \frac{1}{2}m_2v_2^2[/tex]
here we know all values of speed as we found it in part a) and part b)